Which Jobs Are Most Vulnerable to COVID-19? What an Analysis of the European Union Reveals - Garrote Sanchez, Daniel; Gomez Parra, Nicolas; Ozden, Caglar; Rijkers, Bob (World Bank, Washington, DC, 2020)
This Research and Policy Brief presents measures of labor market exposure to COVID-19 (coronavirus)in the European Union (EU) by identifying jobs in non-essential industries that cannot be performed from home. Jobs most at risk account for 30 percent of all EU employment. These jobs are concentrated in lagging regions; tend to be low paid and less secure; and are disproportionately held by young, poorly educated workers and migrants. In the absence of urgent large-scale remedial action, the COVID-19 (coronavirus) is likely to exacerbate preexisting socioeconomic and regional disparities.